Quality of life and handgrip strength of HIV patients diagnosed with neurotoxoplasmosis - Luiz Fernando Gouvêa-; Cíntia Naira Souza de Lima; Kerolen Tayla Lima Fernandes; Silvania Yukiko Lins Takanashi; Marília Brasil Xavier (Universidade Federal de Santa Catarina, 2019)
HIV / AIDS epidemic continues to be a major public health problem, and when there is poor adherence to treatment, patients become susceptible to other infections such as toxoplasmosis. The aim of this study was to evaluate the handgrip strength and quality of life of HIV infected patients diagnosed with neurotoxoplasmosis. A cross-sectional study was conducted with 40 HIV-infected patients, with and without diagnosis of neuroxoplasmosis. Sociodemographic and clinical profile information was collected, and handgrip strength and quality of life were evaluated. Almost all patients of both groups used antiretroviral therapy. In the handgrip strength evaluation, no statistical difference was observed for the right and left hand between groups with and without neurotoxoplasmosis (p> 0.05). However, the classification of inadequate handgrip strength in the neurotoxoplasmosis group was significantly higher. In the quality of life domain, it was observed that financial concern had lower scores in the group with neurotoxoplasmosis (p = 0.0379). It was observed that neurotoxoplasmosis showed no association with epidemiological, clinical, handgrip strength and quality of life variables. However, patients with neurotoxoplasmosis showed a trend towards lower muscle strength.